UNDERSTANDING THE PUBLIC INTEREST IN DEVELOPMENT NYIA (New Yogyakarta International Airport): AN ECONOMIC ANALYSIS AND LEGAL APPROACH - Muhammad Fikri Alan (Yustisia Jurnal Hukum, 2019)
This paper seeks to use economic and law approaches in looking at the problems that occur over the construction of New Yogyakarta International Airport (NYIA). According to the legal approach that is often done, it has not given a clear meaning of what the phrase "public interest" is. In fact, the meaning of this phrase becomes very important, considering that this is used as the basis by the state in seizing the right to land owned by people, which is then used for the construction of the airport. For the economic approach method, it is expected to be able to complete the approach, by analyzing whether the current development process can benefit the country economically or not. Thus, the use of economic approaches, in this case is the NYIA's development policy, in fact, can be ambiguous. On the one hand it can be a justification for the state to continue the development process. On the other hand, it can be a justification for the people who until now continue to expect the development of the NYIA to be halted.